Engaging Diverse Audiences at the Archaeological Open-air Museum Düppel in Berlin – Practical Examples and New Strategies - Julia Heeb (EXARC, 2019)
In 1939, a boy called Horst Trzeciak was playing on a piece of land on the outskirts of Berlin. While playing, he found a number of pottery sherds. In an exemplary fashion he brought the sherds to the “Märkisches Provinzialmuseum”, which was, at that time, the city museum of Berlin. The sherds were identified as medieval and catalogued. After WWII, the city of Berlin was divided, the “Märkisches Provinzialmuseum” landed on the eastern side of the wall. Archaeologists working in the western part of Berlin began researching the medieval colonization of Berlin and Brandenburg. While investigating potential sites for research excavations, they came across the sherds found in 1939. As the sherds could be dated to the medieval period around 1200 AD, the site was deemed suitable for better understanding the change in settlement patterns during that period. From 1967, the site was excavated as part of a DFG project (DFG=German Research Association).